Modern ideas about the pathogenesis of gestational diabetes mellitus - Mohamed L. Leffad; Nadezhda M. Startseva; Said M. Semiatov; Nadiya K. Kizima; Milana H. Mashtagova (LLC "MEDIAFORMAT", 2024)
Aim. Gestational diabetes mellitus (GDM) is by far the most common type of metabolic disorder in pregnant women, the consequences of which are significant for doctors of various specialties. Features of the course of GDM determine a whole range of completely new problems associated with the health of newborns. This was influenced, on the one hand, by the obesity pandemic, which provoked an exponential increase in the incidence of GDM, and insulin resistance, responsible for the earlier onset of GDM, and on the other hand, by the introduction into clinical practice of clear unified diagnostic criteria adopted by major international medical associations. As the prevalence of GDM continues to increase, the development of new prognostic and diagnostic tests for this pregnancy-associated condition is of great importance to improve outcomes for both mothers and children. Purpose. To study modern ideas about the pathogenesis of GDM. Material and methods. To write this review, a search was carried out for domestic and foreign publications in Russian and international search systems (PubMed, eLibrary, etc.) over the past 9 years. The review included articles from the peer-reviewed literature. Results. The review presents data on various mechanisms of GDM occurrence. Conclusion. Thus, GDM is a growing public health problem associated with rising obesity. To minimize complications for mother and baby, early diagnosis is essential. However, ideal screening for GDM has not yet been developed. The studies discussed in this review highlight the seriousness of GDM, including identifying and managing risk factors, accurately diagnosing and treating the disease to prevent associated complications.